Trajetórias de docentes universitários com a temática ambiental: do mito de origem às ações no campo ambiental - Monte, Maria das Graças (Universidade Federal de São Carlos, 2013)
This research is aimed at having deeper knowledge of the challenges faced by a group of university professors to consolidate academic practices with the environmental thematic, having the path of their personal and professional lives as reference, presented by means of biographical narratives. Throughout this study there is an attempt to identify: what are the factors related to the admittance and permanence of professors in the environmental field; what are the mediating elements in the construction processes of academic practices with the environmental thematic; what are the factors inherent to their actions, which move them towards consolidating environmental culture in the academic context. The interpretation of the content in the narratives was based on the theoretical contribution by Isabel Cristina de MouraCarvalho with regards to myths of origin, means of access and rites of admittance to the environmental field; by Hannah Arendt, on the conception of action, and by René Kaes on the conception of intermediate. The results analysis reveals that the childhood experiences of being close to nature, the participation in the social movements in the 70 s and the qualification as an academic researcher are memories brought out from memory, which delineate the myth of origin. The presence of formation of intermediaries in the academic context allowed professors to consolidate academic practices with the environmental thematic. In the absence of these formations remain the conflicts and crisis that, despite jeopardizing advances, don t stop the mobilization of professors for action, for new constructions.The professors actions are mainly found in setting academic practicesoriented by collectivity principles, which highlight the issue of creating groups as space forfruitful dialogues in order to consolidate environmental culture in the academic context.
Keywords: Educação ambiental; Trajetórias de docentes universitários; Práticas acadêmicas; Temática ambiental; Environmental thematic; Trajectories of academics; Academic practices; CIENCIAS HUMANAS::EDUCACAO